The method by which Cephenemyia trompe (Modeer) larvae invade reindeer (Rangifer tarandus) - Anderson, John R.; Nilssen, Arne C. (Rangifer, 1990)
Laboratory electrostimulated C. trompe (Modeer) females forcefully expelled (sprayed) larvae for 5-20 cm. The watery spray consisted of about 20 tiny droplets containing two to several larvae. Crawling first-instar larvae exhibited negative geotactic and phototropic responses; they were subject to rapid desiccation and became immobile as the tiny droplets dried within a few seconds. When 5-50 larvae from dissectedfemales were dropped in physiological saline onto different areas of the muzzle of restrained reindeer, only larvae placed deep within the nostrils and on the lips crawled out-of-sight down the nostril passage or into the mouth. Drops of larvae placed elsewhere quickly desiccated and the larvae became immobile. Larvae deposited by wild females onto a COz-baited reindeer model with the muzzle, lips and nostrils coated with insect trapping adhesive all were stuck only along the dorsal lip below the philtrum. All experimental evidence supports a natural per os mode of invasion.